2010
DOI: 10.1111/j.1469-8137.2010.03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channels in photosynthetic eukaryotes: implications for evolution of calcium‐based signalling

Abstract: SummaryMuch of our current knowledge on the mechanisms by which Ca 2+ signals are generated in photosynthetic eukaryotes comes from studies of a relatively small number of model species, particularly green plants and algae, revealing some common features and notable differences between 'plant' and 'animal' systems. Physiological studies from a broad range of algal cell types have revealed the occurrence of animal-like signalling properties, including fast action potentials and fast propagating cytosolic Ca 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(178 citation statements)
references
References 208 publications
(389 reference statements)
6
171
1
Order By: Relevance
“…Na V s are thought to have evolved as a result of gene duplication and diversification of an ancestral Ca V , as the four domains of Na V s show higher sequence similarity to the corresponding domains of Ca V s than to each other and have in turn the lowest levels of similarity with K V s (Hille, 1989). Moreover, the fact that Ca V s have a wider phylogenetic distribution than Na V s supports this scenario as well (Verret et al, 2010) (see below). The discovery of bacterial sodium-selective channels (NaChBac) (Ren et al, 2001;Yue et al, 2002;Koishi et al, 2004) has somewhat blurred the evolutionary history of Ca V s and Na V s as NaChBac genes encode a single 6-TM domain that assembles into a tetramer (Durell and Guy, 2001;Ren et al, 2001;Payandeh et al, 2011), and as their selectivity pattern resembles that of animal Na V channels but their filter sequence resembles that of Ca V s, it was suggested that NaChBac channels rather than K V s might be the true ancestors of animal Na V s and Ca V s (Charalambous and Wallace, 2011).…”
supporting
confidence: 51%
See 2 more Smart Citations
“…Na V s are thought to have evolved as a result of gene duplication and diversification of an ancestral Ca V , as the four domains of Na V s show higher sequence similarity to the corresponding domains of Ca V s than to each other and have in turn the lowest levels of similarity with K V s (Hille, 1989). Moreover, the fact that Ca V s have a wider phylogenetic distribution than Na V s supports this scenario as well (Verret et al, 2010) (see below). The discovery of bacterial sodium-selective channels (NaChBac) (Ren et al, 2001;Yue et al, 2002;Koishi et al, 2004) has somewhat blurred the evolutionary history of Ca V s and Na V s as NaChBac genes encode a single 6-TM domain that assembles into a tetramer (Durell and Guy, 2001;Ren et al, 2001;Payandeh et al, 2011), and as their selectivity pattern resembles that of animal Na V channels but their filter sequence resembles that of Ca V s, it was suggested that NaChBac channels rather than K V s might be the true ancestors of animal Na V s and Ca V s (Charalambous and Wallace, 2011).…”
supporting
confidence: 51%
“…Hence, it would seem that four-domain Ca V s would be widespread in protozoa. Surprisingly, they are absent in many protist lineages (Verret et al, 2010), although well represented in a few lineages such as ciliates. Most of the increases in cytosolic Ca 2+ influx in protists appear to be through ligand-gated channels, transient receptor potential (TRP) channels or internal stores.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Benthic Euglena species, which are common in microphytobenthic biofilms and also show vertical migratory rhythms (Palmer & Round, 1965;Kingston, 1999Kingston, , 2002, probably share the same form of graviperception with planktonic species of the same genus. Furthermore, diatoms possess voltage-and mechanosensitive calcium channels, whose operation is linked to rapid changes in membrane potential (Taylor, 2009), and increases in cytosolic calcium concentration as a response to mechanical stimulus have been reported for Phaeodactylum tricornutum (Falciatore et al, 2000;Verret et al, 2010). Also, the operation of calcium ion channels and changes in cytosolic concentration are known to be involved in benthic diatom motility (Cohn & Disparti, 1994;McLachlan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, rapid and local Ca 2+ signals generated in the cytosol depend on a Ca 2+ current driven by a steep concentration gradient between the cytosol (nanomolar range) and its adjacent organelles or extracellular space (millimolar range). This allows the induction of a rapid and strong Ca 2+ rise in the cytosol required for immediate activation of an appropriate response by the simple opening of a few Ca 2+ channels [25] [26]. A calcium signature (characterized by amplitude, duration, frequency and location) can encode a message that contributes to a specific physiological response, after downstream decoding.…”
Section: Introductionmentioning
confidence: 99%